The Dolenc technique was used to clip 14 cases of ruptured basilar apex aneurysms and posterior cerebral artery aneurysms - Hongwei, Zhang; Kang, Xie; Aimin, Li; Dong, Zhang (Frontiers in Neurology, 2022)
Objective: To investigate the surgical techniques and their clinical effects for ruptured basilar artery apex and posterior cerebral aneurysms via the Dolenc approach. Methods: We retrospectively analyzed the clinical data of 14 patients with ruptured basilar artery apex and posterior cerebral aneurysms, who underwent surgical clipping by Dolenc approach from July 2017 to June 2020 in Beijing Tiantan Hospital affiliated to Capital Medical University and Lianyungang Hospital affiliated to Xuzhou Medical University. The modified Rankin scale (mRs) scores were used to evaluate the prognosis of patients. Results: All 14 cases of aneurysm were successfully clipped. Overall, 1, 2 and 1 case of postoperative new-onset visual loss, oculomotor nerve palsy and contralateral hemiplegia, respectively, were reported. Digital subtraction angiography (DSA) or Computed tomography angiography (CTA) examination of the aneurysm within 2 weeks after surgery revealed that the aneurysm was completely clipped without residue. The observations during the follow-up within 12–18 months after surgery were as follows: 1 case of vision loss returned to normal, 2 cases of oculomotor nerve palsy, 1 case of return to normal, 1 case of improved, 1 case of contralateral hemiplegia improved after rehabilitation treatment and 1 case of hydrocephalus ventriculoperitoneal shunt surgery was performed. Overall, 11, 2 and 1 case had mRs scores of 0, 1 and 2, respectively. No death was reported. Conclusion: For the small number of basilar apical and posterior cerebral aneurysms treated non-invasively, the Dolenc approach may offer advantages over other modalities.